Features of practical application of electric power system’s stability estimation methods - V. V. Barskov; A. V. Bubnov; A. N. Kirichenko (Омский научный вестник)
Timeliness of the topic is conditioned by the need to keep up ample of static and transient stability margins in modern electrical power systems. The article object is to give a determination of present methods of evaluating damping of systems with synchronous machines, in the context of their effectiveness. And also to estimate the effectiveness of these methods in the performance of the task concerned with selecting best settings of automatic excitation regulators of synchronous generators. This analysis led us to the conclusions, in particular, about possibility to apply the root locus methods in estimating stability of electrical power systems, and also about genericity of the matrix method with the use of QR-algorithm, which is widely used in practice of calculating stability